Aeroelastic Coupling between a Thin Divergent and High Pressure Jets - Schall, Eric; Lardat, Raphael; Dervieux, Alain; Koobus, Bruno; Farhat, Charbel (European Journal of Computational Mechanics, 2000)
Rocket divergents concentrate the engine thrust on a light structure. This thrust may provoke deformations, and these deformations may influence the jet. For analysis, we formulate a coupled fluid/structure/moving grid problem, which leads to a numerical model involving a three-field Arbitrary Lagrangian- Eulerian method offering second-order spatial accuracy. It employs a time-staggered procedure for global second-order accurate time-integration of the corresponding coupled semi-discrete equations. We present the transient aeroelastic response obtained with a simplified geometry of divergent when the flow condition induces shock waves either behind or inside the nozzle, for structural designs of small stiffness.